2004
DOI: 10.1017/s0952836903004394
|View full text |Cite
|
Sign up to set email alerts
|

Habitat segregation between sympatric Tibetan argali Ovis ammon hodgsoni and blue sheep Pseudois nayaur in the Indian Trans‐Himalaya

Abstract: Tibetan argali Ovis ammon hodgsoni and blue sheep Pseudois nayaur have almost completely overlapping distributions encompassing most of the Tibetan plateau and its margins. Such a sympatric distribution of related species with similar ecological requirements implies that there is some degree of resource partitioning. This may be accomplished on the basis of habitat and/or diet separation. This study evaluated such ecological separation on the basis of physical habitat partitioning by these two sympatric ungula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 26 publications
7
53
0
Order By: Relevance
“…The sheep maintained proximity to cliffs or bare rock (Wilson, 1981;Harris and Miller, 1995;Oli, 1996;Namgail et al, 2004). Similar results were obtained in this study but blue sheep from the present study showed no significant difference in slope direction and degree between winter and spring (Table 1).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The sheep maintained proximity to cliffs or bare rock (Wilson, 1981;Harris and Miller, 1995;Oli, 1996;Namgail et al, 2004). Similar results were obtained in this study but blue sheep from the present study showed no significant difference in slope direction and degree between winter and spring (Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…It is unfortunate that these studies were restricted in some particular seasons (Harris and Miller, 1995;Namgail et al, 2004;Liu et al, 2005), in a few habitat variables (Wilson, 1981;Harris and Miller, 1995;Oli, 1996;Namgail et al, 2004), and in insufficient plots (Oli, 1996;Wilson, 1981;Harris and Miller, 1995). Due to the shift of food resources from winter to spring, we predict that winter foraging sites by blue sheep should show some differences from spring sites.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Rachlow & Bowyer, 1998;Singh et al, 2009). Many mountain ungulates evade predation by fl eeing to precipitous, so called 'escape' terrain (Geist, 1971;Namgail et al, 2004). However, build as more of a coursing animal, argali typically descend from escape terrain and fl ee from potential predators (Namgail et al, 2004;Walker et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Many mountain ungulates evade predation by fl eeing to precipitous, so called 'escape' terrain (Geist, 1971;Namgail et al, 2004). However, build as more of a coursing animal, argali typically descend from escape terrain and fl ee from potential predators (Namgail et al, 2004;Walker et al, 2007). Predators, especially domestic dogs and wolves, represent the leading cause of mortality for argali sheep in Ikh Nart Nature Reserve on the northern edge of Mongolia's Gobi (Reading et al, 2009).…”
Section: Resultsmentioning
confidence: 99%